2011
DOI: 10.1186/1748-717x-6-29
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles in human cancer cells after ionizing radiation

Abstract: IntroductionMicroRNAs are regulators of central cellular processes and are implicated in the pathogenesis and prognosis of human cancers. MicroRNAs also modulate responses to anti-cancer therapy. In the context of radiation oncology microRNAs were found to modulate cell death and proliferation after irradiation. However, changes in microRNA expression profiles in response to irradiation have not been comprehensively analyzed so far. The present study's intend is to present a broad screen of changes in microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
83
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 23 publications
1
83
0
1
Order By: Relevance
“…Significantly, certain miRNAs have been identified to consistently show characteristic changes postirradiation across a range of different cancers. For example, expression of several members of the let-7 family, a well-known tumor suppressor and regulator of the K-Ras oncogene, were found to be affected by radiation exposure (29,30,(32)(33)(34)(35). Most members of the let-7 family (except let-7g) have been found to be downregulated in irradiated fibroblasts (33), lung cancer cells (30) or colon cancer cells (35).…”
Section: Mirnas To Monitor Response To Radiotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…Significantly, certain miRNAs have been identified to consistently show characteristic changes postirradiation across a range of different cancers. For example, expression of several members of the let-7 family, a well-known tumor suppressor and regulator of the K-Ras oncogene, were found to be affected by radiation exposure (29,30,(32)(33)(34)(35). Most members of the let-7 family (except let-7g) have been found to be downregulated in irradiated fibroblasts (33), lung cancer cells (30) or colon cancer cells (35).…”
Section: Mirnas To Monitor Response To Radiotherapymentioning
confidence: 99%
“…Most members of the let-7 family (except let-7g) have been found to be downregulated in irradiated fibroblasts (33), lung cancer cells (30) or colon cancer cells (35). However, in irradiated glioma and squamous cell carcinoma cell lines REVIEW some members of the let-7 family are upregulated (29,34). Another two miRNAs, miR-21 and miR-34, are consistently upregulated in various benign and malignant cell lines after irradiation (28, 34, 36-38).…”
Section: Mirnas To Monitor Response To Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Radioresistance adds another barrier to treatment efficiency in GBM. Not surprisingly, Niemoeller et al's ana lysis of human glioma cells demonstrated upregulation of miRNA clusters after treatment with clinically relevant radiation doses [19]. These results are somewhat expected as miRNAs can also be targets of molecular therapy, and those involved in apoptosis or regulating the expression of specific genes may induce the apoptosis of tumor cells exhibiting radioresistance [20].…”
mentioning
confidence: 94%